Answer:
n= -17
Explanation:
Simplifying
5 + n + (15 + -2) = 0
Combine like terms: 15 + -2 = 13
5 + n + (13) = 0
5 + n + 13 = 0
Reorder the terms:
5 + 13 + n = 0
Combine like terms: 5 + 13 = 18
18 + n = 0
Solving
18 + n = 0
Solving for variable 'n'.
Move all terms containing n to the left, all other terms to the right.
Add '-18' to each side of the equation.
18 + -18 + n = 0 + -18
Combine like terms: 18 + -18 = 0
0 + n = 0 + -18
n = 0 + -18
Combine like terms: 0 + -18 = -18
n = -18
Simplifying
n = -18